Iris scanning phenomenon within the regulatory framework - Muzzio Arguello, Javier Maurucio (2024)
This report deals with the phenomenon of iris scanning for money, which in recent years, led by companies such as Worldcoin, has gained popularity due to the promise of financial gains in exchange for biometric data. We will also discuss the legal framework in different parts of the world, its statistics, current measures and opportunities, trends and challenges